Design of air-aspiration drum type tray precision seeding streamline - MA Guang (浙江大学学报. 农业与生命科学版)
Aimed at lack of automated assembly line in the domestic vegetable seedling production field, combined with the seeding process of domestic vegetable seeds, the air-aspiration drum type tray precision seeding streamline was designed. The assembly line included an unpowered pressure hole device, a drum-inlaid convex suction nozzle, and a seeding machine for conveying and drum synchronous transmission. The data of air-aspiration drum type tray precision seeding steamline was showed as follows: seeding precision of 98%, seeding cavity rate of 0.6%, productivity of 580 disks/h, seeding amount of 145 disks/(kW·h), and seed breakage rate of 0.4%. The above data shows that the technical indicators of the streamline meet the standards, and the design is reasonable and reliable, which can satisfy the needs of the actual use of the streamline.